DINAMIKA PSIKOLOGIS SISWA UNDERACHIEVER DALAM SISTEM PENDIDIKAN KOMPETITIF - Imam Baidhawi (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigates the psychological dynamics of underachieving students those with high cognitive potential but low academic performance within Indonesia’s competitive educational system. Employing a qualitative narrative and phenomenological approach, the research engaged 20 junior and senior high school students from five top-performing schools, all of whom had IQ scores ≥120 yet consistently performed below class averages. Findings revealed four dominant psychological factors contributing to underachievement: (1) misalignment between individual learning styles and standardized curricula, (2) maladaptive perfectionism that fosters a fear of failure, (3) evaluation anxiety, and (4) social alienation within academic environments. Thematic analysis uncovered how competitive pressure exacerbates underachievement through mechanisms such as self-handicapping and learned helplessness, where students unconsciously create barriers to protect their academic self-concept. The study highlights the need for a reimagined educational strategy, advocating for differentiated curricula, strength-based counseling, and teacher training to support gifted students at risk of underachievement. This research offers new insights into the necessity of holistic and humane approaches to foster student potential in competitive yet uniform academic systems.